2021
DOI: 10.1038/s41598-021-01279-2
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of non-adopters of COVID-19 non-pharmaceutical interventions through a national cross-sectional survey to assess attitudes and behaviours

Abstract: Adoption of non-pharmaceutical interventions (NPIs) remains critical to curtail the spread of COVID-19. Using self-reported adherence to NPIs in Canada, assessed through a national cross-sectional survey of 4498 respondents, we aimed to identify and characterize non-adopters of NPIs, evaluating their attitudes and behaviours to understand barriers and facilitators of adoption. A cluster analysis was used to group adopters separately from non-adopters of NPIs. Associations with sociodemographic factors, attitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 56 publications
(59 reference statements)
6
14
0
Order By: Relevance
“…This means the more dangerous the virus is considered to be, the more willing a person is to take protective action. These findings confirm further crosssectional studies such as Lang et al (37) showing that people who were unconcerned that an infection with the virus might lead to severe symptoms had higher odds of being non-adopters of non-pharmaceutical preventive interventions. Furthermore, in a sample of over 6,600 persons in the US, Bruine de Bruin and Bennett also found people that considered high risk to be associated with an infection with the coronavirus to be more likely to adopt protective behaviors (44).…”
Section: Perceived Health Risksupporting
confidence: 89%
See 3 more Smart Citations
“…This means the more dangerous the virus is considered to be, the more willing a person is to take protective action. These findings confirm further crosssectional studies such as Lang et al (37) showing that people who were unconcerned that an infection with the virus might lead to severe symptoms had higher odds of being non-adopters of non-pharmaceutical preventive interventions. Furthermore, in a sample of over 6,600 persons in the US, Bruine de Bruin and Bennett also found people that considered high risk to be associated with an infection with the coronavirus to be more likely to adopt protective behaviors (44).…”
Section: Perceived Health Risksupporting
confidence: 89%
“…The survey revealed that higher age and female gender were independent predictors of adherent behavior. Even though previously published studies were inconclusive, a large percentage of studies support our results (23,24,(37)(38)(39). For example, one Canadian study of over 2,000 persons between 18 and 100 years old showed that age and male gender were associated with lower adherence to different COVID-19 protective measures such as working remotely from home, social distancing, and maintaining a physical distance of 2 m from others (23).…”
Section: Age and Gendersupporting
confidence: 77%
See 2 more Smart Citations
“…In the fields of public health and social psychology, many studies reflect on attitudes towards and the adoption of specific NPIs (e.g., Kantor & Kantor, 2020 ; Lang et al, 2021 ; Shen et al, 2021 ; Xu et al, 2020 ), as well as on pharmaceutical interventions (PIs) like vaccines (e.g., Cascini et al, 2021 ; Seddig et al, 2022 ; Soveri et al, 2021 ). Among the few who have investigated NPIs in a tourism context, Lee et al (2012) , for example, showed that they had a positive effect on tourists’ intentions to travel internationally during the 2009 H1N1 influenza pandemic.…”
Section: Introductionmentioning
confidence: 99%